Comparison of antibacterial effect of calcium hydroxide combined with chlorhexidine and povidone-iodine against Enterococcus faecalis in dentinal tubules of human incisors: An in vitro comparative study - Sameer Punathil; Shabna Moyin; Sham S Bhat; Sundeep Hedge; Archana Pai; Jeswin James (Wolters Kluwer Medknow Publications, 2020)
Background and Objectives: It has been found that the microorganism behind the failure of root-filled teeth is Enterococcus faecalis, which shows resistance to most of the intra-canal medicaments. Therefore, the purpose of this study was to evaluate the antibacterial efficacy of three intra-canal medications-calcium hydroxide with saline, combinations of calcium hydroxide with 2% chlorhexidine (CHX), and calcium hydroxide with 5% povidone-iodine-against E. faecalis in dentinal tubules of human incisors. Materials and Methods: Forty permanent maxillary central incisors were made into standardized segments and infected with E. faecalis. They were treated with a paste made of calcium hydroxide and 2% CHX, calcium hydroxide and 5% povidone-iodine, and calcium hydroxide and saline for 1 week. Dentinal shavings collected from the canal were suspended in thioglycollate broth solution and spread on brain heart infusion agar. Colony-forming units (CFUs) were enumerated and the CFU per milligram of dentin was calculated. The pH of the medicaments used was measured with the help of pH meter. Results: The results showed that the paste made from calcium hydroxide and 2% CHX was significantly more effective than that made from calcium hydroxide and povidone-iodine, and calcium hydroxide and saline. The addition of CHX or povidone-iodine did not affect the alkalinity of calcium hydroxide. Conclusion: This study concludes that Ca(OH)2 + 2% CHX are effective against E. faecalis. Combinations of calcium hydroxide and 5% povidone-iodine showed better antibacterial effect than calcium hydroxide and saline. Ca(OH)2 + saline was ineffective against E. faecalis.